The Influence Of Fisheries Production, Labor, And The Number Of Fisheries Households On Economic Growth In Dumai City In 2012-2023 - Hanif Adhitya Ananda; Yelly Zamaya (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Economic growth is an effort to increase production capacity to achieve additional output. this study aims to analyze the effect of fisheries production, labor, and the number of fishery households on economic growth in Dumai City in 2012-2023. this research was conducted in Dumai City, Riau Province. the research used is quantitative with secondary data in the form of time series. Data obtained from the official website of the Dumai City Statistics Agency, and one data owned by the Dumai City Fisheries and Marine Service. the data was analyzed with SPSS software. this study resulted in fisheries production and the number of fishermen having an influence on economic growth while fishery households have no influence on economic growth because fishery households are more likely to survive to fulfill their own needs, without having a meaningful impact on macroeconomic growth in Dumai City.